Antecedents of Outpatient Satisfaction in Internal Medicine Polyclinic during Covid-19 Pandemic Era (Empirical Study At Hospital X) - Meidy C. Elim; Ferdi Antonio (Medical Scope Journal, 2022)
Abstract: There is high competition among private hospitals in seeking the quality of health services provided that meets consumer needs. The largest service unit in the hospital is the outpatient unit; one of the polyclinics is Internal Medicine unit. Patients coming for treatment in this unit during the COVID-19 pandemic expect the best health services. A variety of factors can affect patient satisfaction but only a few studies are focused on outpatient satisfaction in the COVID-19 pandemic era so far. This research aimed to evaluate the effects of environment and facilities, professional competence, caring attitudes and emotional support, perceived compliance of COVID-19 protocol, communication and information, and waiting time on patient’s satisfaction. There were 164 samples obtained by purposive sampling from respondents that filled out the online questionnaires. Data were analyzed by using the PLS-SEM. The results showed that the independent and mediating variables had significant positive effects on general satisfaction. The strongest effect was from environment and facilities and professional competence, while the direct effect on general satisfaction was found to be the strongest from waiting time. In conclusion, the results confirmed the theory of patient satisfaction with health services. Therefore, this research model has strong predictive accuracy and large predictive relevance to be used and developed in further research. Keywords: satisfaction; outpatient; COVID-19; private hospitals